2010
DOI: 10.1007/s00401-010-0768-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytoskeletal abnormalities in the neuropathology and pathophysiology of type I lissencephaly

Abstract: Type I lissencephaly or agyria-pachygyria is a rare developmental disorder which results from a defect of neuronal migration. It is characterized by the absence of gyri and a thickening of the cerebral cortex and can be associated with other brain and visceral anomalies. Since the discovery of the first genetic cause (deletion of chromosome 17p13.3), six additional genes have been found to be responsible for agyria–pachygyria. In this review, we summarize the current knowledge concerning these genetic disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 171 publications
(311 reference statements)
0
46
0
Order By: Relevance
“…Cortical malformations are recovered in the human populations at a surprisingly high rate and can be familial or arise spontaneously de novo (1)(2)(3)28). One manifestation of cortical malformation is subcortical band heterotopia (SBH) and lissencephaly (LIS; smooth brain).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical malformations are recovered in the human populations at a surprisingly high rate and can be familial or arise spontaneously de novo (1)(2)(3)28). One manifestation of cortical malformation is subcortical band heterotopia (SBH) and lissencephaly (LIS; smooth brain).…”
Section: Discussionmentioning
confidence: 99%
“…We thus used dendrite enhancement by Dcx expression as an assay for wild type Dcx function, using previously described MT binding-competent and MT bindingdeficient mutants (25)(26)(27). All of these alleles were originally identified in patients with lissencephaly (2,28,29). We found that Dcx alleles that retain MT binding but lack the C-terminal regions (required for spn and AP adaptor binding) are defective for dendrite growth promotion (i.e.…”
mentioning
confidence: 99%
“…7 Functional studies suggest that abnormal neuronal migration would result from defective interactions in the tubulin heterodimer assembly and altered three-dimensional conformation of the tubulins, with compromised interaction with microtubule-associated proteins or microtubule motors. 11 This study brings to eight the number of individuals with TUBB2B mutations reported so far. We identified three new TUBB2B mutations in as many unrelated patients with rather symmetrical malformations of cortical development, including polymicrogyria in two patients, one having a cobblestone-like cortex, and bilateral regional pachygyria in one.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Reelin interacts, via membrane receptors, with motor and cytoskeletal proteins [94,95], likely targets of calcium dependent pathways. Actually, it has been shown that the product of the LIS1 gene, whose mutation leads to Type I lissencephaly, regulates in a calcium influx-dependent way some RhoGTPases involved in cytoskeletal dynamics [96].…”
Section: Calcium Signalling and Neuronal Migration Disordersmentioning
confidence: 99%
“…It can be envisioned that future focus will be, more than on calcium signalling per se, on the field of calcium-dependent proteins involved in cytoskeletal organization and in organelle trafficking, as pointed by the Reelinlissencephaly case [94][95][96]. However, it cannot be excluded that the TRP channel superfamily, just a newcomer in this context, may provide some surprise -and some unexpected answers.…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%